Pengaruh Brand Image, Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Sandal Crocs Di Kota Batam - Setiawan, Fero; Suhardi , Suhardi (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the effect of Brand Image, Product Quality, and Promotion on Purchase Decisions of Crocs sandals in Batam City. The research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 119 respondents who are consumers of Crocs products in Batam City. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis, using SPSS version 26. The results indicate that Brand Image and Product Quality have a positive and significant effect on Purchase Decisions. Meanwhile, Promotion shows a positive but insignificant effect on Purchase Decisions. Simultaneously, Brand Image, Product Quality, and Promotion have a positive and significant effect on Purchase Decisions. The Adjusted R Square value of 0.905 indicates that 90.5% of the variation in Purchase Decisions can be explained by the three independent variables, while the remaining 9.5% is influenced by other factors not examined in this study. This research is expected to provide insights for companies in formulating more effective marketing strategies, particularly in strengthening brand image and improving product quality.